Measuring health confidence: benefits to patients, clinicians and healthcare providers - Tim Benson; Alex Benson (BMJ Open Quality)
Background Patients need a high level of health confidence to manage their own care with success. However, health confidence is complex and changes throughout life.Methods The Health Confidence Score (HCS) is a measure of a patient’s confidence and has four items covering their opinion of their health knowledge, ability to self-care, get help and participate in shared decision-making, plus an aggregate summary score. It is a short, easy-to-use measure with a low reading age.Data from about 5000 ratings are analysed, coming from anonymised patients living out of hospital.Results Findings show a highly significant improvement in health confidence between referral and follow-up after care and treatment. Health confidence is inversely related to the number of medications taken. The highest health confidence is in patients aged between 30 and 49. The lowest health confidence is in patients aged between 50 and 69. No significant difference in health confidence between male and female patients. Health confidence is a different concept from health status and personal well-being.Conclusion Integrating HCS into routine care fosters patient-centred healthcare, promotes self-care and can reduce cost of care.